Ambivalent Cosmopolitanisms : Literature, Embalmment and Postcolonial Mobilities [Cosmopolitismes ambivalents : Littérature, embaumement et mobilités postcoloniales] - Srilata Ravi (Essays in French Literature and Culture)
This reading, through the lens of ambivalent cosmopolitanisms, of one of Maryse Condé’s lesser-known novels, Les belles ténébreuses (2008), demonstrates that the Guadeloupean writer’s engaged writing does not represent hybridity, mobility and navigability as uncritical features of a globalized world. It argues that the use of literary grotesque in the narration and representation of the protagonists, Ramzi and Kassem, underlines postcolonial cosmopolitanism’s inherent paradoxes and inconsistencies.